Heterogeneity of hemoglobin H disease in childhood - Brain, Joseph D.; Christophi, Costas A. (My University, 2011)
As Lal et al. (Feb. 24 issue) emphasize, α-thalassemia has profound consequences as a chronic disease that leads to anemia and multiple manifestations of iron toxicity. In an editorial in the same issue, Benz supports the conclusion that thalassemias are now more common because of globalization. Both the article and the editorial endorse newborn screening. Although we agree with the above, we also believe that primary prevention of α-thalassemia and β-thalassemia, both of which are inherited in an autosomal recessive fashion, should be recommended. In the Republic of Cyprus, the incidence of thalassemia has decreased dramatically during the past several decades, and the proportion of Cypriot babies born with β-thalassemia has decreased to less than 10% of the former level. This decrease was accomplished by increasing public awareness, counseling, prenatal diagnosis, and premarital screening, which is now required. An additional strategy is to use in vitro fertilization after prescreening to ensure that only thalassemia-free embryos are implanted.4 A complete approach to minimizing the impact of genetic diseases should include prevention as well as early diagnosis and appropriate medical interventions.
Keywords: Alpha-Thalassemia; Hemoglobin H; Hemoglobin Constant Spring